The Pesticides Use by Rice Farmers in Siak Regency - Sri Swastika; Rusli Rustam; Hafiz Fauzana (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2022)
The use of chemical pesticides is still considered for rice farmers to be one of the most effective ways for pest control. The chemical content in pesticides is toxic and causes an increased risk for farmers and the environment if their use is not under applicable regulations. The limited knowledge of farmers about the application of Integrated Pest Management (IPM) and lack of discipline in the use of pesticides has triggered environmental damage, especially the lowland rice ecosystem and human health. This study aims to determine the use of pesticides by rice farmers in Siak Regency in controlling rice pests. The method used is a purposive sampling interview method using a questionnaire. The results showed that rice farmers had not implemented a pest control system based on the IPM principle, which did not pay attention to the control threshold as a basis for pesticide use. Farmers are satisfied with the effectiveness of chemical pesticides in pest control, so they continue to use them in rice farming. The lack of Farmers' knowledge about IPM and its application can trigger farmers to increase the dosage and frequency of spraying if the chemical pesticides used are not able to control the pest.